Kinetic of Dehydration of CuSO4+5H2O - YUYE, YU (Asian Journal of Chemistry, 2010)
Thermal decomposition of CuSO4·5H2O was studied under non-isothermal conditions in air. The kinetic of particular stages of CuSO4·5H2O decomposition were evaluated from the dynamic weight loss data by the means of integral method and differential method. The values of the activation energy E, the pre-exponential factor A of each stages of the thermal decomposition were calculated. The entropy of activation (ΔS≠), the enthalpy of activation (ΔH≠), the free energy of activation (ΔG≠) and kinetic compensation effect were also studied.